EFEK KONSUMSI MINUMAN BUBUK KAKAO (Theobroma cacao L.) BEBAS LEMAK TERHADAP SIFAT ANTIOKSIDATIF LIMFOSIT SUBYEK PEREMPUAN [The Effect of Fat Free Cocoa (Theobroma Cacao L.) Powder Drinks Consumption on Antioxidative Activity of Lymphocyte of Women Subjec - . Erniati; Fransiska R. Zakaria; Bambang Pontjo Priosoeryanto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2012)
The health benefits of cocoa both in vivo and in vitro have been reported in many studies. Cocoa is a rich source of flavonoids known to have antioxidant activity, such as catechin, epicatechin and procyanidin. The aim of this research was to evaluate the effect of fat free cocoa powder drink consumption on antioxidative properties and proliferation activities of woman lymphocyte. Healthy woman subjects were divided into cocoa group (n = 9) and control group (n = 9). Cocoa powder drink containing skim milk and sugar was given to the cocoa groups every morning for 25 days. The control group received only water containing skim milk and sugar. Both cocoa and control group received physical medical checkup at the beginning and at the end of the intervention. Their peripheral blood was taken for lymphocyte antioxidant analysis. The measured antioxidant properties consisted of antiradical activity by DPPH method, malonaldehyde (MDA) and glutathione levels. The data of cocoa group showed that there was a significant increase (p ≤ 0.05) in antiradical level from 31+11.2 to 40.19+7.42% and glutathione from 48.2±10.5 to 66.7±15.9 μmol/land a decrease in MDA level in the lymphocyte (p < 0.05) from 2.98±2.21 to 1.29±0.33 μmol/las compared to the control group (from 25.77±6.9 to 26.79±6.12%; 34.7±20.7 to 37.8±19.2 μmol/land 3.01±1.53 to 2.069±0.707 μmol/l respectively) after consumption of the cocoa powder drink. The results of this research revealed that fat free cocoa powder has a strong antioxidant activity which was manifested up to the blood cells.